2005
DOI: 10.1111/j.1067-1927.2005.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic denervation accelerates wound contraction but delays reepithelialization in rats

Abstract: Participation of the peripheral nervous system in wound healing is not well understood. The aim of this study was to investigate the effects of sympathetic denervation on rat excisional cutaneous wound healing. Male rats were chemically denervated with intraperitoneal administration of 6-hydroxydopamine (6-OHDA) in 1% ascorbic acid. 6-OHDA or vehicle was administered twice a week until euthanasia, beginning 7 days before wounding. A full-thickness excisional lesion was performed and the lesion area measured to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 32 publications
5
46
1
Order By: Relevance
“…Denervated corneas are associated with a defective epithelial attachment to the basement membrane zone (2). In the epidermis, damage to sympathetic or sensory nerves is known to impair reepithelialization (46,47). Innervation is also critical for scarless fetal wound healing of the skin (48).…”
Section: Discussionmentioning
confidence: 99%
“…Denervated corneas are associated with a defective epithelial attachment to the basement membrane zone (2). In the epidermis, damage to sympathetic or sensory nerves is known to impair reepithelialization (46,47). Innervation is also critical for scarless fetal wound healing of the skin (48).…”
Section: Discussionmentioning
confidence: 99%
“…While a number of different cell types can undertake phagocytosis, macrophages are professional phagocytes, a specialized subset of immune cells that respond to activation and differentiation signals by modulating their phagocytic efficiency (25). Norepinephrine, the primary neurotransmitter of the peripheral sympathetic nervous system, is released in large quantities from peripheral nerves into the circulation following injury and has previously been shown to be involved in wound healing (26)(27)(28)(29). While a number of studies report catecholamine-mediated alterations in the phenotype of splenic and peritoneal macrophages (20,21,30), the present study is the first to delineate a role for norepinephrine in modulation of wound macrophage phagocytic function.…”
Section: Discussionmentioning
confidence: 99%
“…Epinephrine or norepinephrine adrenoceptors, stress-released catecholamines,have been implicated in the pathophysiology of delayed wound healing of cutaneous lesions, acting by delaying the migration and activation of macrophages and neutrophils, inhibiting keratinocyte migration and re-epithelialization in vitro and in vivo wound models [22][23] . Besides alteration of cellular activity related to inflammation, catecholamines stimulate vasoconstriction that causes hypoxia at the wound area and the increase of endothelial cell proliferation, vascular endothelial growth factor (VEGF) expression and angiogenesis.…”
Section: Effect Of Propranolol On Capsular Reaction Around Silicone Imentioning
confidence: 99%
“…Propranolol now is used as a first-line treatment in infantile hemangiomas when intervention is required [19][20][21] . Since propranolol's invention by Sir James Black and co-workers in 1960s 19 , it has been demonstrated that the peripheral nervous system has important participation in wound healing and that beta-blockers modulates stress-related injury, both wound healing and inflammation, facts that attracted the interest of numerous scholars and led to various hypotheses [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation